Analysis of Multicultural Values in Cross-Cultural Studies Textbooks for Elementary Schools Teacher - Kamil, Nurdin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The purpose of this study was to describe the multicultural values contained in cross-cultural study teaching materials and the form of application of multicultural values in learning in elementary schools. The method used in this research is qualitative research with data sources, namely cross-cultural study textbooks. Data collection techniques in the form of documentation using data recording instruments and attachments. The data analysis technique used is qualitative analysis. The results showed that there are multicultural values in cross-cultural study teaching materials, namely (1) the value of tolerance; (2) the value of unity and integrity; (3) cooperation; (4) solidarity. In addition, a form of application of multicultural values by integrating multicultural values in subjects in elementary schools.